2019
DOI: 10.3390/jmse7050140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Girder Spacing and Depth on the Solitary Wave Impact on Coastal Bridge Deck for Different Airgaps

Abstract: Coastal bridge damage has become a severe issue of concern in the recent past with the destruction of a considerable number of bridges under the impact of waves during tsunami and storm surges. These events have become more frequent, with waves reaching the bridge deck and causing upliftment and destruction. Past studies have demonstrated the establishment of various theoretical equations which works well for the submerged deck and regular wave types but show much scatter and uncertainty in case of a deck that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Montoya et al (2019) numerically evaluated two damaged bridges in Hurricane Katrina using the Coupled Eulerian-Lagrangian (CEL) approach in Abaqus and analyzed the effects of foundation flexibilities on the uplift and shear forces. Moideen et al (2019) generated solitary wave in the open source model REEF3D and studied its vertical impact force on the bridge deck. Qu et al (2019b) implemented the SIFUM-FVCOM multiscale system to study the hydrodynamic loads on coastal highway bridges under the impact of real-world tsunami.…”
Section: Low-rise Bridgementioning
confidence: 99%
“…Montoya et al (2019) numerically evaluated two damaged bridges in Hurricane Katrina using the Coupled Eulerian-Lagrangian (CEL) approach in Abaqus and analyzed the effects of foundation flexibilities on the uplift and shear forces. Moideen et al (2019) generated solitary wave in the open source model REEF3D and studied its vertical impact force on the bridge deck. Qu et al (2019b) implemented the SIFUM-FVCOM multiscale system to study the hydrodynamic loads on coastal highway bridges under the impact of real-world tsunami.…”
Section: Low-rise Bridgementioning
confidence: 99%
“…This case is often used as a reference for numerical simulations to evaluate the representation of flow phenomena using a simple geometry (Eaton and Johnston 1981, Le et al 1997, Ratha and Sarkar 2015, Chovet et al 2018, Wang et al 2019). Johnston (1988a, 1988b) More recently, studies such as Seiffert et al (2015), Moideen et al (2019) and Seiffert et al (2014) have started to look into total vertical forces of solitary and cnoidal waves on coastal bridge decks with openings where entrapped air has the potential to add to the overall force balance by increasing buoyancy. For future studies, it would be crucial to investigate the destabilizing effect of entrapped air within structures exposed to extreme flow conditions, such as broken solitary waves or bores.…”
Section: Uplift Forcesmentioning
confidence: 99%
“…Seiffert et al (2015) experimentally analysed the effects of air relief openings and found a significant reduction of vertical uplift forces when large openings are present. Further, Moideen et al (2019) built upon the experimental data to perform a parametric study on vertical impact forces with the computational fluid dynamics (CFD) model REEF3D (Bihs et al 2016), analysing the effect of wave heights, girders spacing and depth for varying air gaps. That study confirmed higher vertical impact forces for bridge decks with girders where air can be trapped.…”
Section: Introductionmentioning
confidence: 99%
“…They employed Ansys commercial software for solving RANS equations with the k-omega turbulence model in this numerical study. The solitary wave forces on a coastal bridge deck were investigated by Moideen et al [15]. The effects of the girder spacing and girder depth were considered on a coastal bridge deck.…”
Section: Introductionmentioning
confidence: 99%